ANALISIS USAHA AGROINDUSTRI MAKANAN PADA UKM BERKAH KOTA PEKANBARU - Sari, Mega Melda; Rifai, Ahmad; Tety, Ermi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This study aims to analyze the agroindustry enterprises in the UKM Berkah Pekanbaru city. Analysis of the data used in this study is the cases study method. The type of data that is collected were primary data and secondary data. Primary data were obtained from the employers include: the amount and price of production factors, the type of raw materials, auxiliary materials, labor, equipment and machinery used and other necessary data. Secondary data were obtained from the monthly reports of business which include: general state of the business, a brief history of the business, coupled also with other data that support this research both from the relevant agencies as well as from other literature. The results of this study indicate that the UKM Berkah Pekanbaru city deserves to be developed with a gross income of Rp 18.4 million, - per month, net income of Rp 5,478,338, - RCR with values ​​of 1.42 and BEP revenue of Rp 7,962,337,-. Food marketing channels in the agroindustry UKM Berkah Pekanbaru city consists of two channels where the first channel (entrepreneurs to consumers) to absorb sales of 23.16% and 76.84% for the second channel (employers distribute products through middlemen 1; supermarkets and airports in Pekanbaru intersection of three and middlemen 2; supermarket on the market down to the next-to-consumer). Overall consumer attitudes towards food product attributes the UKM Berkah Pekanbaru city is the price and followed with the texture, flavor, brand and packaging. Sweet and delicious taste of another product is the top choice of consumers in purchasing. The savory and crunchy texture of the UKM Berkah Pekanbaru city food become second reason of consumers in making a purchase. Keywords : UKM Berkah, Analysis, Product Income